Measuring the Retained Water and Sequestered Organic Carbon Contents of Soil Profiles in Aroostook and Piscataquis Counties, Maine, USA. Issue 6 (31st October 2013) - Ghabbour, Elham A.; Davies, Geoffrey; Sayeed, Abeer A.; Jenkins, Tony
Abstract : Humic acids (HA) and fulvic acids (FA) are sequestered carbon compounds in soils that can be measured reliably with gravimetric and spectrophotometric methods, respectively. As part of the ongoing National Soil Project at Northeastern University, this paper reports the HA and FA contents of soil horizons from agricultural (potatoes in rotation with small grains and broccoli) and forestry land uses in northern Maine, USA. The agricultural fields are depleted in HA and FA compared to nearby woodland soils of similar provenance. We confirm that HA are better soil water retainers than total organic matter (OM) components on an equal mass basis. Humification starts at the soil surface and HA, FA, and dissolved organic carbon (DOC) contents drop sharply below the O and A horizons. The depleted OM, HA, FA, and DOC contents of spodosol horizons in soil profiles can be quantified. Fulvic acids in the Maine soils investigated are in a solid‐solution equilibrium with a HA·FA(s) /FA(aq) ratio of about 3.4:1. From the correlation of DOC (g L −1 ) and FA(g L −1 ), FA in the Maine soil samples contain about 54% carbon. The HA and FA are long‐lived soil components that represent the baseline OM content of any soil. As such they are a sink in the carbon cycle that needs to be maintained in agricultural soils, including those in Aroostook and Piscataquis Counties of Maine.